THE CHOICE OF SOLVENT FOR ADHESIVES BASED ON STYRENEISOPRENE THERMOPLASTIC ELASTOMERS - L. R. Lyusova; A. Y. Selina; M. V. Khlyustina; Yu. A. Naumova; S. G. Karpova (Тонкие химические технологии)
In this paper concentrated and dilute solutions of a styrene-isoprene thermoplastic elastomer in volatile organic solvents of different nature and films formed of them were studied. The influence of the solvent on the complex of technological and operational properties of the adhesive compositions is shown.